Money Circulation in the Bulgar Ulus in the second half of fourteenth century - Mukhametshin D.G. (Золотоордынское обозрение)
Research objectives: To reveal the radical change in money circulation in the second half of the fourteenth century, using the example of the coin hoards of the Bulgar ulus and the 199 excavation of the Bolgar settlement. Research materials: These include the hoards of the Bolgar settlement, the Karatunsky hoard, and counter-minted coins from the 199 excavation of the Bolgar settlement. Results and novelty of the research: The city of Bolgar began to resume minting coins after it was annexed to the ulus of Jochi. The earliest such coins were minted on behalf of the Caliph an-Nasir and the Great Khans, Möngke and Ariq Böke. After the establishment of the Golden Horde, Bolgar minted coins on behalf of Mengu-Timur and subsequent rulers, as well as many anonymous and unepigraphic coins that have been found deposited in hoards. Hoards are an indicator of changes in monetary circulation in the ulus and they increased significantly during the reign of Toqtamish Khan. Counter-minted and trimmed coins appeared due to a shortage of coins; this is a characteristic feature of the monetary circulation of the Bulgar ulus.